Lower Jurassic beds with bivalves in south Slovenia - Buser, Stanko; Debeljak, Irena (Geologija, 1994)
The Lower Jurassic beds of south Slovenia outcrop on a surface of several hundred km2 with their thickness in places exceeding 300 meters. They were deposited on the Dinaric Carbonate Platform. In them rich accumulations of characteristic bivalves occur that in Pliensbachian and Toarcian inhabited the wide interconnected shallow water regions of the western and Southern margins of Tethys and the eastern Pacific. The most interesting are three large bivalve species: Lithiotis problematica, Cochlearites loppianus and Lithiopedalion scutatus. in addition, numerous other genera can be found: Gervilleioperna, Mytilus, Opisoma and Pachyrisma (with subgenera Pachymegalodon and Durga). The bivalves formed in the region of south Slovenia, in the prevailingly quiet environment of the restricted shelf, sea-bottom mats or biostromes. Their shells can be only rarely found in their growth position. The horizon with bivalves (“lithiotid horizon”) in south Slovenia is attributed to Pliensbachian (Domerian). It is up to 75 metres thick and it almost does not pinch out. Within it individual lumachelles of bivalves occur which are from several centimetres to ten metres thick. They are almost exclusively associated with dark, micritic, in places marly limestone and bituminous dolomite. The biodiversity in lumachelles is very low. The intermediate beds that do not contain bivalves mostly consist of oolitic and biosparitic limestone. In this article some localities from various areas of the carbonate platform are described. Considered are paleogeographical and paleoecological conditions that permitted the existence of this typical bivalve fauna.